Hubungan Pola Asuh Orang Tua dengan Perkembangan Motorik Kasar pada Anak Prasekolah di PAUD Mutiara Qur’an RW 07 Banyuanyar Kota Surakarta - Assarah Valentina Febriyanti; Maryatun Maryatun (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
During the preschool period, children's growth is stable, this can be seen from the aspect of physical development or motor development, the most important factor that can affect gross motor development is parenting, because parenting is a way that parents do in encouraging children to achieve goals. To analyze the relationship between parenting patterns and gross motor development in preschool children at Paud Mutiara Qur'an RW 07 Banyuanyar Surakarta City. The type of research used quantitative with a cross sectional approach with a sample of 67 respondents. Data were collected through questionnaires and KPSP sheets. Based on parenting patterns, namely democratic parenting patterns as many as 47 respondents, and based on the incidence of gross motor development that is in accordance with the development of 46 students. Analysis with the chi square test shows that there is a relationship between parenting patterns and gross motor development in preschool children at Paud Mutiara Qur'an Rw 07 Banyuanyar Surakarta City (p-value = 0.000). The existence of good parenting can encourage children to achieve the desired goals, such as the development of gross motor development in preschool-age children so that children can follow development according to their age stage.